ASMA: towards adaptive secured multipath in MANETs - Toubiana, Vincent (2006)
As they are used to create open communities, Mobile Ad hoc NETworks (MANETs) are not favourable environments to establish trust, which is necessary to provide security. Multipath routing mechanisms within infrastructureless networks environment seems appropriate and useful to enhance security protection. In fact, the level of trust can be increased so as many of potential security attacks are detected, revealed and stopped. Nevertheless an excessive control overhead is always generated. In this paper, we propose a global framework that integrates a set of concepts and mechanisms aiming at enhancing security in highly dynamic decentralized ad hoc networks. Our solution focuses on authentication, routing securing, trust management with reliable estimation of trust. A large panoply of attacks are prevented using our various mechanisms.